APPLICATION OF COMPETENCE MODELS IN PUBLIC SECTORS: REFLECTING THE DISRUPTION ERA - James Kalimanzila; Suryanto Suryanto (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The purpose of this study is to access and describe the application and development of competence models in public sectors particularly in the disrupting era. The development of technology, organization change and innovation have increased the necessity and application of competency models in public sectors based on hard and soft human skills. However, private sectors are doing well in applying competence models compared to public sectors. Moreover, public organization systems in the World have undergone many different reforms in order to handle and copy with issues happening in disrupting era. In this study, a qualitative research method was used based on explaining the concept of competence model, drawing insights from theories, reading different articles and publications. Furthermore, competency model is a very essential tool in human resource systems and public institutions practice because it guides and develops human resource skills, knowledge and behavioral that enable an employee to perform their job effective particularly in the challenging era. We would like to suggest that public institutions must apply competence models and create quick strategic basic reforms in order to undergo and copy with new changes or challenges like what private sectors do in dealing with disrupting issues. Keywords: application, competence, competence model, public sector, disruption era